Analysis of Personal Hygiene, Household Sanitation Status of Lungs Tuberculosis Nutrition - Mariana Mariana; Emma Novita; Pariyana Pariyana; Annisa Muthia Haryani; Rifqoh Trikurnia (Majalah Kedokteran Sriwijaya, 2020)
Nutritional status determines the level of health and function of all vital systems in the body, including the immune system. The immunization system as a host of various infectious diseases. Cell-mediated immunity in the body plays an important role as a defense against tuberculosis. Therefore, malnutrition can be considered as an important consideration factor in Tuberculosis efforts. The impact of malnutrition is so severe that there is an increase in the prevalence of Tuberculosis associated with HIV infection. Many factors cause Tuberculosis, some debates are Environment. Environmental factor is one that affects home lighting, humidity, temperature, conditions, roofs, walls, floors and residential density. Besides environmental factors there are also other factors which consist of gender, age, income, hygiene knowledge and practices as well as knowledge about resistance to tuberculosis also influencing the increase in disease. The purpose of this study is to collect data that will help prevent many complications from tuberculosis, especially those caused by malnutrition and hygiene in the neighborhood. Research Object: Patients in Palembang City Health Center Work Area. Research Location: Palembang City Health Center Work Area. This research is an observational analytic study of categorical comparative hypothesis testing with a cross-sectional research design. The results of the analysis of the chi-square test were 0.000 <0.05 there is a relationship between the incidence of malnutrition in pulmonary TB patients with the sanitary conditions of the patient's home environment. Relationship between Personal Hygiene and Nutritional Status of Lung TB The results of the analysis of the chi-square test were 0.000 <0.05. Conclusions and Suggestion From the results of this study there are still many bad personal hygiene that can have an impact on Tuberculosis. In addition, poor environmental sanitation has an effect on Tuberculosis. Therefore, this research needs to be continued to determine the impact of poor home environmental sanitation and personal hygiene. Further education and counseling must be carried out by the general public regarding information about Tuberculosis